2019
DOI: 10.1111/cas.13936
|View full text |Cite
|
Sign up to set email alerts
|

ZNF671 DNA methylation as a molecular predictor for the early recurrence of serous ovarian cancer

Abstract: Serous ovarian cancer is the most frequent type of epithelial ovarian cancer. Despite the use of surgery and platinum‐based chemotherapy, many patients suffer from recurrence within 6 months, termed platinum resistance. Currently, the lack of relevant molecular biomarkers for the prediction of the early recurrence of serous ovarian cancers is linked to the poor prognosis. To identify an effective biomarker for early recurrence, we analyzed the genome‐wide DNA methylation status characteristic of early recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…This might offer utility in improving survival outcomes of patients with ovarian cancer (Fang et al, 2018). Another recent study has highlighted the tumor suppressor role of ZNF671 and its methylation could act as a predictor for early recurrence of serous ovarian carcinoma (Mase et al, 2019). Another important study by M. Keita et al has for the first time reported the exclusive association of massive DNA hypomethylation with poorly differentiated tumors, which correlates with disease aggressiveness and progression.…”
Section: Predictivementioning
confidence: 99%
“…This might offer utility in improving survival outcomes of patients with ovarian cancer (Fang et al, 2018). Another recent study has highlighted the tumor suppressor role of ZNF671 and its methylation could act as a predictor for early recurrence of serous ovarian carcinoma (Mase et al, 2019). Another important study by M. Keita et al has for the first time reported the exclusive association of massive DNA hypomethylation with poorly differentiated tumors, which correlates with disease aggressiveness and progression.…”
Section: Predictivementioning
confidence: 99%
“…Furthermore, multiple genes were validated to be mediated by aberrant DNA methylation, acting as diagnostic, treatment, and prognostic markers for esophageal squamous carcinoma [16]. Also, the methylation status of ZNF671 was utilized as an independent marker for predicting ovarian cancer recurrence [20]. As with these different kinds of tumors, a series of methylation-related gene dysregulation has been detected in HNSCC, including p16, CDH1, DAPK and MGMT [21], implying their potential functions in HNSCC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that DNA methylation can be a promising biomarker in cancer. DNA methylation of NKD1, RUNX3, and ZNF671 were reported to be predictors of progression-free survival (PFS) in patients with OC [9][10][11]. Furthermore, a previous study reported that a DNA methylation signature can predict overall survival in patients with OC [12].…”
Section: Introductionmentioning
confidence: 99%